2021
DOI: 10.1021/acs.iecr.1c02058
|View full text |Cite
|
Sign up to set email alerts
|

Current Trends and Approaches to Boost the Performance of Metal Organic Frameworks for Carbon Dioxide Methanation through Photo/Thermal Hydrogenation: A Review

Abstract: Because of the increasing energy demand of the growing human population, the world is facing a crisis of depleting fossil fuels as well as huge amounts of CO 2 emissions being put into the environment. Therefore, to combat these two major issues, catalytic CO 2 hydrogenation is introduced which utilizes the abundant CO 2 in the atmosphere and at the same time generates clean fuel and chemicals. Metal organic frameworks (MOFs) are a very attractive catalyst for the conversion of CO 2 into CH 4 due to their high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 231 publications
0
20
0
Order By: Relevance
“…CO is also an important intermediate product and plays a key role in the process of photocatalytic reduction of CO 2 . 56–58 The adsorption/desorption properties of CO on the surface of the catalyst greatly affect the formation of CH 4 . 59,60 Therefore, in order to better understand the product selectivity of CO 2 reduction over the PtCu cocatalysts, it is necessary to further explore the adsorption and conversion process of CO on the surface of the PtCu cocatalysts.…”
Section: Resultsmentioning
confidence: 99%
“…CO is also an important intermediate product and plays a key role in the process of photocatalytic reduction of CO 2 . 56–58 The adsorption/desorption properties of CO on the surface of the catalyst greatly affect the formation of CH 4 . 59,60 Therefore, in order to better understand the product selectivity of CO 2 reduction over the PtCu cocatalysts, it is necessary to further explore the adsorption and conversion process of CO on the surface of the PtCu cocatalysts.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogenation of CO 2 can be used to synthesize valuable compounds: (1) hydrocarbons, such as methane (CH 4 , the reaction can be called methanation), [270,274] olefins, and gasoline, or (2) other compounds, such as formic acid (HCOOH), alcohol (e.g., methanol), and carbon monoxide (CO). [10,[264][265][266][267][268][269][270][271][272][273] Hydrogenation can be promoted via electrochemical, [275] thermo-catalysis, [276] and photo/thermal [277] methods. ZIF materials are promising catalysts in terms of efficiency and selectivity among several catalysts.…”
Section: Hydrogenation For Comentioning
confidence: 99%
“…Currently, as highly porous and structurally tunable light-responsive materials, MOFs have extremely promising prospects in the catalytic conversion of CO 2 . They have a large specific surface area and high porosity, which can not only be used as a gas adsorbent to capture CO 2 but also generate electron–hole pairs under light illumination to promote the reaction. Wang et al designed an ultramicroporous Ti–MOF (MIP-208), the first MOF composed of Ti–O helical chains and the isophthalate linker as shown in Figure e, on which RuO x was deposited, and the composites exhibited excellent CO 2 conversion performance under photothermal conditions . It was revealed that the reaction followed the main operating mechanism of the photocatalytic methanation, causing CO 2 reduction and H 2 oxidation by the photoinduced charge separation state instead of a photothermal pathway by increasing the local temperature through replacing H 2 with a better electron donor and less photothermal conversion materials.…”
Section: Catalyst Development For Photopromoted Carbon Dioxide Methan...mentioning
confidence: 99%